Investigating the Use of Research-Based Information by Educational Practitioners in Finland and the UAE - Soukieh, Ali (2021)
Soukieh, Mohammad Ali. 2021. Investigating the Use of Research-Based Information (RBI) by Educational Practitioners in Finland and the UAE. University of Jyväskylä. Faculty of Education and Psychology. 54 pages.